(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
This article presents monitoring of the distribution of the wild boar population in Karakalpakstan. As a result of research work, it was established that wild boars are widespread in the Lower Amu Darya delta, around natural lakes and artesian wells in the north-west of the Kyzylkum, as well as in areas between the cracks of the Northern Ustyurt plateau and the Aral Sea